The ring of confidence: a haloarchaeal CRISPR/Cas system. (29th January 2013) - Maier, Lisa-Katharina; Stoll, Britta; Brendel, Jutta; Fischer, Susan; Pfeiffer, Friedhelm; Dyall-Smith, Mike; Marchfelder, Anita
Abstract : To survive the constant invasions by foreign genetic elements, prokaryotes have evolved various defensive systems. Almost all sequenced archaea, and half of the analysed bacteria use the CRISPR (clustered regularly interspaced short palindromic repeats)/Cas (CRISPR-associated) system, a recently identified prokaryotic immune system that can fend off invading elements in a sequence-specific manner. Few archaeal CRISPR/Cas systems have been analysed so far, and the molecular details of many of the steps involved in adaptation and defence are yet to be understood. In the present paper, we summarize our current knowledge about the CRISPR/Cas system in Haloferax volcanii, an extremely halophilic archaeon that was isolated from the Dead Sea. H. volcanii encodes a type I-B CRISPR/Cas system, and carries three CRISPR loci and eight Cas proteins. Although in laboratory culture for more than three decades, this defence system was shown to be still active. All three CRISPR loci are transcribed and processed into mature crRNAs (CRISPR RNAs). Cells challenged with engineered plasmids can recognize and eliminate these invading elements if they contain the correct PAM (protospacer adjacent motif) and a sequence that can be recognized by one of the CRISPR spacers.